The Influence of Green Investment and Corporate Social Responsibility Towards Corporate Value Through Corporate Performance as a Mediating Variable - Abdurrohman; Sunardi; Edi Subiyantoro (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study aims to analyze the influence of Green Investment and Corporate Social Responsibility on Company Value and How Company Performance mediates the relationship between Green Investment and Corporate Social Responsibility . The practical contribution of this study is as a reference for business actors and stakeholders in the business world to increase company value through company performance by implementing Green Investment and Corporate Social Responsibility more effectively. This research is quantitative with secondary data. The population in this study is all companies that achieved the Corporate Performance Rating Program in Environmental Management (PROPER) during 2022-2023, totaling 3,694 companies. While the sample used in this study uses a purposive sampling technique . The criteria are (1) Companies listed on the IDX and consistently achieved PROPER ratings during 2022-2023, (2) Companies that consistently report their annual reports during 2022-2023. With these criteria, a sample of 50 companies was obtained that met the criteria with the number of data collected being 100 data. The data analysis method used is Path Analysis . The results of the study show that Green Investment has a significant positive effect on company performance, while Corporate Social Responsibility does not show a significant effect on company performance , company performance is proven to have a significant positive effect on company value , while Green Investment and Corporate Social Responsibility does not have a significant effect on company value . Mediation analysis reveals that company performance acts as a full mediator for Green Investment . Conversely , Corporate Social Responsibility not utilizing company performance as a channel to influence the company's value.